Dasar Pertimbangan Penyidik dalam Penerapan Restorative Justice Pada Tindak Pidana Pencabulan Terhadap Anak (Studi Kasus di Polresta Metro) - Nurcholissa, Ayyusita; Shafira, Maya; Raisa Monica, Dona; Susanti, Emilia (UNIVERSITAS SERAMBI MEKKAH, 2025)
This research aims to analyze the basis of investigators' considerations in using restorative justice as a resolution mechanism for child sexual abuse cases at the Metro City Police Resort. The research employed normative and empirical juridical approaches. Primary and secondary data were collected through literature reviews and field studies. Data were analyzed qualitatively to draw conclusions aligned with the issues discussed. The findings indicate that the investigators' considerations in resolving child sexual abuse cases are based on juridical, philosophical, and sociological foundations. Juridically, the Metro City Police Resort refers to Article 16 Paragraph (1) of Law No. 2 of 2002 on the Indonesian National Police regarding discretion and Police Regulation No. 8 of 2021 on the Handling of Criminal Acts Based on Restorative Justice. Philosophically, the application of restorative justice in such cases is rooted in the principles of substantive justice and the protection of human rights, particularly for vulnerable child victims. Sociologically, restorative justice in this context considers the circumstances of the perpetrator and the victim, as well as the impact caused by the crime. To ensure the perpetrator fulfills their obligations, the police must monitor the implementation of agreements made during the restorative justice process. This monitoring is crucial to prevent recidivism by the perpetrator and ensure the victim receives ongoing protection and recovery.